شیخ الحدیث روح الامین ؒ کی شخصیت اور اُن کی دینی و سماجی خدمات کاتحقیقی جائزہ: Research Evaluation of the Personality of Sheikh Al-Hadith Roohul-Amin and his Religious and Social Services (Khairulummah, 2022)
Allah Ta'ala has given a very high rank to the scholars. About which he said:﴿ وَٱلَّذِينَ أُوتُواْ ٱلۡعِلۡمَ دَرَجَٰت﴾"And those who have been given knowledge, Allah will raise them in ranks".Therefore, the services of scholars should be brought before the people so that people can follow them and live in the light of Quran and Hadith. One of them is Rabbani scholar Abul Zia Roohul Amin. Whose teachings, compilations and writings and Sufism and self-purification passed. Now his life and academic services should be described so that the people can learn from his routines and lifestyles and take guidance from him.